The interrelation between HIV and condyloma acuminata high-risk strain: HIV AND CONDYLOMA ACUMINATA - Yuliarto, Danu; Mawardi, Prasetyadi; Irawanto, Muhammad Eko (Journal of Pakistan Association of Dermatologists, 2023)
Background Condyloma acuminata (CA) is a sexually transmitted infection (STI) due to human papillomavirus (HPV). HPV Infection generally occurs through small gaps in the epithelial surface of the skin and mucous membranes. There are more than 280 types of HPV identified to infect humans. Strains 16 and 18 are oncogenic since they are strongly associated with cervical dysplasia, which can progress to malignancy. Human Immunodeficiency Virus (HIV) is an immunosuppressive disease that causes the number of CD4+ T lymphocytes, macrophages, NK cells, and neutrophils to decrease, causing changes in immunity and modulating the occurrence of HPV infection. The purpose of this study is to determine the relationship of high-risk HPV (HR-HPV) strain with IHC staining between HIV and non-HIV patients. Methods This study is cross-sectional research that involved 41 CA patients who underwent a biopsy to obtain histopathological data. A consecutive non-random sampling technique was used to select the subjects. The subjects were divided into CA with HIV and CA with non-HIV, we devide the subjects with ELISA examination. The IHC staining was subsequently performed to determine the HR-HPV strain. The finding was interpreted based on immunoreactive cells. Result The average age of the HR-HPV strains group was 31.20 Â± 16.87 years, and the average age of its negative strains was 33.19 Â± 12.41 years (p=0.931). HIV-positive patients were 5 (100%) with HR-HPV, yet none was found in HIV-negative. Conversely, 12 patients (33.3%) are HIV-positive patients with low risk (LR)-HPV and 24 HIV-negative patients (66.7%) with LR-HPV. Statistic results showed a significant relationship between HIV incidence and HR-HPV (p=0.005). Patients with negative HR-HPV have a 0.810 times lower risk of HIV than positive HR-HPV. Conclusion This study demonstrated that negative HR-HPV was a protective effect of HIV. CA patients with HIV infection were examined for high-risk CA strains with IHC staining to help determine prognosis and therapy.